The last lie - Forde, Patricia (Sourcebooks Young Readers, 2020)
Letta is an illegal Wordsmith charged with collecting and keeping all words in the city of Ark, a place where everyone is required to only speak List, a language of just 500 words. She and other rebels called Creators vow to protect free speech that allows the people of Ark to express themselves and be fully human. When the rebels are captured, Letta goes on the run, still striving to preserve language while the vicious new ruler of Ark unleashes a frightening new plan to eliminate speech once and for all by keep all the city's babies from ever hearing the spoken word.